(untitled) (Janaki Medical College Journal of Medical Science, 2022)
NO is a gas and has a very short half-life (3-5s), as it is highly reactive. No and its products are inactivated through oxidation into nitrite (NO2-) and nitrate (NO3-) Which is excreted in the urine. NO is regarded as magical molecule which has profound role in regulation of various function in various organs of human body and in health and disease. Here in this review article authors has discussed about its chemistry and metabolism, its discovery, its basic functions, role in pathophysiology of various diseases and its therapeutic implications.